Peramalan Suhu Rata – Rata Kota Padang Panjang dengan Membandingkan Metode SARIMA dan Holt – Winter Additive - Putri, Fadhira Vitasha; Ikhsan, Easbi; Fitri, Fadhilah (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2024)
Padang Panjang City, situated at an altitude of 650 to 850 meters above sea level and surrounded by high mountains, experiences significant temperature changes that affect various aspects of life such as public health, agriculture, and tourism. This study aims to forecast the monthly average temperature of Padang Panjang City from January 2017 to December 2023 by comparing SARIMA and Holt-Winters Additive forecasting methods. The results show that the SARIMA method, with an MSD value of 0.2206, is more accurate compared to the Holt-Winters Additive method, which has an MSD value of 0.29821. With the SARIMA model as the best method, the forecast indicates that the highest average temperature in Padang Panjang City will reach 23.1418 degrees Celsius in May 2024. These results are expected to provide a strong basis for planning and decision-making related to the temperature changes occurring in Padang Panjang City.